Faith, Healing and Medicine in the time of COVID-19 - Wild-Wood, Emma (My University, 2022)
Faith shapes the way societies respond to crises such as a global pandemic. Dr Emma Wild-Wood, from the University of Edinburgh in the UK, is studying how faith informs responses to the COVID-19 pandemic in the Democratic Republic of Congo, one of Africa's poorest countries.

La foi détermine la manière dont les sociétés réagissent à des crises telles qu'une pandémie mondiale. Madame Dr. Emma Wild-Wood, de l’Université D’Edinburgh au Royaume-Uni, étudie l'influence de la foi sur les réponses à la pandémie du COVID-19 en République démocratique du Congo, l'un des pays les plus pauvres d'Afrique.
Dr Emma Wild-Wood has been collaborating with researchers in DR Congo to understand how faith communities there have been impacted by COVID-19. Here is some material developed for UK secondary schools to show how religious studies can help global health studies.
Keywords: global health; public health; COVID-19; faith communities; religion; Democratic Republic of Congo; Africa